Clinical And Hormonal Characteristics of Osteoporosis in Patients With 2- Type of Diabetes - Maxammatjonova Asalxon Bozorboy qizi (Periodica Journal, 2024)
Arterial hypertension is a strong and variable risk factor for the development of macrovascular and microvascular complications of diabetes. Patients with diabetes mellitus belong to the group with a high and very high risk of developing cardiovascular complications and chronic kidney diseases. The combination of type 2 diabetes and hypertension dramatically increases the risk of developing terminal stages of microvascular and macrovascular diabetic complications, blindness, end-stage chronic kidney disease, amputation of legs, myocardial infarction, cerebral strokes, worsens prognosis and quality of life
Keywords: arterial hypertension; nephropathy; hyperglycemia